2021
DOI: 10.7759/cureus.13742
|View full text |Cite
|
Sign up to set email alerts
|

Limited Scleroderma-Induced Pulmonary Arterial Hypertension Resulting in Impaired Postoperative Respiratory Function

Abstract: Limited scleroderma falls under the umbrella of systemic sclerosis, an autoimmune disease that presents with multiorgan dysfunction that includes pulmonary arterial hypertension. We examine a case of pulmonary arterial hypertension in an elderly nonsmoker with a history of limited scleroderma. The patient presented with abdominal tenderness and was diagnosed with a sigmoid colonic stricture. She underwent laparoscopic bowel resection. During and after her surgery, she suffered from worsening respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…As an inflammatory autoimmune disorder with diffuse involvement of various organs, systemic sclerosis can be manifested by pericardial effusion. The prevalence of clinically symptomatic pericardial effusion (PE) in SSc is 5-16% 1 .On the other hand, the prevalence of pulmonary artery hypertension (PAH) in SSc (Systemic sclerosis-induced PAH (SSc-PAH)) has been reported to be around 10-15%, with a higher prevalence in limited cutaneous type 2 . Some studies have concluded that pulmonary hypertension in systemic sclerosis is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As an inflammatory autoimmune disorder with diffuse involvement of various organs, systemic sclerosis can be manifested by pericardial effusion. The prevalence of clinically symptomatic pericardial effusion (PE) in SSc is 5-16% 1 .On the other hand, the prevalence of pulmonary artery hypertension (PAH) in SSc (Systemic sclerosis-induced PAH (SSc-PAH)) has been reported to be around 10-15%, with a higher prevalence in limited cutaneous type 2 . Some studies have concluded that pulmonary hypertension in systemic sclerosis is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 On the other hand, the prevalence of pulmonary artery hypertension (PAH) in SSc (systemic sclerosisinduced PAH (SSc-PAH)) has been reported to be around 10%-15%, with a higher prevalence in limited cutaneous type. 2 Some studies have concluded that pulmonary hypertension in systemic sclerosis is associated with a poor prognosis. Vascular endothelial damage, inflammation, and fibrosis are possible mechanisms involved in the pathogenesis of SSc-PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial damage, inflammation, and fibrosis are possible mechanisms involved in the pathogenesis of SSc-PAH. 2 Cardiac tamponade is reported in about 0.02% of PAH cases. 3 Even in the absence of tamponade, based on pulmonary hypertension (PH) guidelines, pericardial effusion in the presence of PH is basically indicative of a high-risk patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations